Quality of Health Information on the Internet for Prostate Cancer - Dwayne T. S. Chang; Robert Abouassaly; Nathan Lawrentschuk (Advances in Urology)
Introduction. To compare (1) the quality of prostate cancer health information on the Internet, (2) the difference in quality between websites appearing earlier or later in the search, and (3) the sources of sponsorship for each of these websites. Materials and methods. The top 150 listed websites on the Google search engine for each of the 11 search terms related to prostate cancer were analysed. Quality was assessed on whether the website conforms to the principles of the Health On the Net Foundation. Each of these websites was then reviewed to determine the main source of sponsorship. Statistical analysis was performed to determine if the proportion of HON accreditation varied among the different cohorts of listed websites and among the 11 search terms used. Results. In total, 1650 websites were analysed. Among these, 10.5% websites were HON-accredited. The proportion of HON-accredited websites for individual search terms ranged from 3.3% to 19.3%. In comparison with the search term of “Prostate cancer,” four search terms had statistically significant odds ratio of the rate of HON accreditation. Websites 51–150 were statistically less likely to have HON accreditation than websites 1–50. The top three website sponsors were journal/universities (28.8%), commercial (28.1%), and physician/surgeon (26.9%). Conclusions. The lack of validated and unbiased websites for prostate cancer is concerning especially with increasing use of the Internet for health information. Websites sponsored or managed by the government and national departments were most likely to provide impartial health information for prostate cancer. We need to help our patients identify valid and unbiased online health resources.